Science/Fiction : A Non-History of Plants. - Aresheva, Victoria; Morette, Clothilde (Leipzig : Spector Books, 2024)
Albin-Guillot, Laure ; Blossfeldt, Karl ; Horst, Horst P. ; Cunningham, Imogen ; Tepe, Richard ; Renger-Patzsch, Albert ; Weston, Edard ; Diederix, Elspeth ; Lempert, Jochen ; Romero, Almudena ; Joseph, Pierre ; Reichmann, Max ; Comandon, Jean ; Green, Walon ; Atkins, Anna ; Bradbury, Henry ; Brakhage, Stan ; Gill, Stephen ; Falls, Sam ; Marder, Michael ; Mesiti, Angelica ; Loderer, Angelika ; Roux, Philippe ; Pallot, Alice ; Deubner, Rebekka ; Tondeur, Anaïs ; Fontcuberta, Joan ; Ruperto, Miljohn ; Heltoft, Ulrik ; Si-Qin, Timur ; False, Éléonore ; Hutchinson, Peter A. ; Aloi, Giovanni ; Murnau, Friedrich Wilhelm ; Staples, Stuart A. ; Smith, Frank Percy ; Kaufman, Philip ; Sekely, Steve ; Francis, Freddie ; Hannam, Ken ; Erickson, Kalev ; Tanaka, Natsumi ; Denes, Agnes ; Kazma, Ali ; Scowen, Charles T. ; Laghouati-Rashwan, Samir ; Dashti, Gohar ; Grotova, Olga ; Polska, Agnieszka ; Sauvage, Ludovic ; Baker, Simon
Science/Fiction: A Non-History of Plants, La Maison Europèenne de la Photographie (MEP), Paris, October 16, 2024 - January 19, 2024
boek